Effect of oxidation temperature and oxygen concentration on macro characteristics of pre-oxidised coal spontaneous combustion process. (15th July 2021) - Lü, Hui-Fei; Deng, Jun; Li, Da-Jiang; Xu, Fan; Xiao, Yang; Shu, Chi-Min
Abstract: Coal fire disasters occur frequently in exposed or underground coal zones or gobs, which usually triggered by pre-oxidised coal spontaneous combustion (PCSC). The thermal mass loss characteristics and thermal effects of pre-oxidised coal with the oxidation temperature and oxygen concentration were investigated. The thermogravimetry (TG) results revealed that the oxidation reaction occurred earlier for the pre-oxidised coal than for raw coal. The pre-oxidised coal had a poor ignition performance and burnout capacity than that of raw coal. In addition, the comprehensive combustion performance of pre-oxidised coal is weaker than that of raw coal, but its combustion rate and short-term combustion intensity are higher than raw coal. The differential scanning calorimetry (DSC) results indicated that the temperature at which the thermal release of pre-oxidised coal increases rapidly lags behind that of raw coal. Moreover, the maximum thermal release power and thermal release for the pre-oxidised coal were less than those for raw coal. The risk of PCSC changes with the increase of oxidation temperature, and there is a critical value of oxidation temperature. When the oxidation temperature was less than the critical value the risk of PCSC is higher than that of raw coal. Furthermore, the critical value decreases with the increase of oxygen concentration.